Seed Mycoflora of Robinia pseudoacacia Linn. and its Control - Sen, Sunita (Indian Forester, 1998)
Eight fungal species Alternaria alternata, Cladosporium sp., Fusarium equiseti, F. oxysporum, F. semitectum, Penicillium chrysogenum, Rhizopus spp. And Ulocladium consortiale were found associated with seeds of Robinia pseudoacacia (Linn.). However, species of Fusarium were found the most predominant ones, and were invariably isolated from seeds samples collected from Bajaura, Manali and Sharbo area of H.P. Amongst the various fungi, Fusarium species and Alternaria alternata were found pathogenic and caused significant reduction in seedling stand. Mercuric chloride (0.1), Baycor (0.25%) and Blitox 50 (0.3%) provided best control of associated mycoflora.